Formation of L12-ordered precipitation in an alumina-forming austenitic stainless steel via Cu addition and its contribution to creep/rupture resistance. (December 2015) - Zhao, Bingbing; Fan, Jifu; Liu, Yize; Zhao, Lin; Dong, Xianping; Sun, Feng; Zhang, Lanting
Graphical abstract: Abstract: Addition of 2.8 wt.% Cu to an alumina-forming austenitic (AFA) stainless steel promotes formation of a L12 -ordered phase with the dominating elements Ni, Cu and Al, instead of B2-NiAl and Cu-rich phases as predicted by the phase equilibrium calculation. At 700 °C/150 MPa, the creep/rupture life of the AFA steel increases from 1537 h to 2047 h with the occurrence of the L12 -ordered phase. The nano-size L12 -ordered Ni–Cu–Al precipitates are uniformly distributed in the austenitic matrix with an average diameter of 35 ± 7 nm even after 2047 h creep/rupture testing.